2021
DOI: 10.3390/md19120699
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Polysaccharide Derived from Laminaria japonica Attenuates Obesity-Related Nonalcoholic Fatty Liver Disease Associated with Gut Microbiota Regulation

Abstract: In this study, the effects of a polysaccharide derived from Laminaria japonica (LJP) on obesity were investigated in mice fed a high-fat diet (HFD). LJP significantly attenuated obesity-related features, lowering serum triglycerides, glucose, total cholesterol and low-density lipoprotein cholesterol levels. HFD-induced liver steatosis and hepatocellular ballooning were significantly attenuated by LJP. Additionally, LJP was found to significantly modulate hepatic gene expressions of AMPK and HMGCR, which are ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…Also, the treatment of tyrosol significantly increased the relative abundance of phylum Verrucomicrobia, which was reported negatively correlated with obesity, and various of phytochemical intervention could promote its colonization. [42] For example, Wang et al [43] reported that apple polyphenol extracts (APE) reduced high carbohydrate dietinduced body-weight gain in C57BL/6 male mice accompanied with increased Verrucomicrobia abundance. Consistent with previous studies, the increased abundance of Verrucomicrobia in our study demonstrated that, tyrosol might be a potential prebiotics nutrient for this microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the treatment of tyrosol significantly increased the relative abundance of phylum Verrucomicrobia, which was reported negatively correlated with obesity, and various of phytochemical intervention could promote its colonization. [42] For example, Wang et al [43] reported that apple polyphenol extracts (APE) reduced high carbohydrate dietinduced body-weight gain in C57BL/6 male mice accompanied with increased Verrucomicrobia abundance. Consistent with previous studies, the increased abundance of Verrucomicrobia in our study demonstrated that, tyrosol might be a potential prebiotics nutrient for this microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Natural polysaccharides, MDG-1, extracted from the roots of Ophiopogon japonicus, inhibits the progression of NAFLD in HFD-fed mice through restoring the gut microbiota balance by improving the abundance of SCFAs-producing the beneficial bacteria, Butyricimonas and Roseburia (Wang et al, 2019) coruscus protects NAFLD in HFD-fed rats, and mechanistically, MPA supplementation reverses HFD-inhibited microbial dysbiosis and SCFAs (Wu et al, 2019a). Soluble polysaccharides from Laminaria japonica attenuates NAFLD in HFD-fed mice by reducing the ratio of Firmicutes/Bacteroidetes, and promoting Verrucomicrobia and propionate-producing bacteria Bacteroides and Akkermansia (Zhang et al, 2021b). Interestingly, the natural polysaccharides are not always safe for the treatment of NAFLD.…”
Section: Hfd-induced Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Mussel polysaccharides, α-D-glucan (MPA) extracted from Mytilus coruscus protects NAFLD in HFD-fed rats, and mechanistically, MPA supplementation reverses HFD-inhibited microbial dysbiosis and SCFAs ( Wu et al, 2019a ). Soluble polysaccharides from Laminaria japonica attenuates NAFLD in HFD-fed mice by reducing the ratio of Firmicutes / Bacteroidetes , and promoting Verrucomicrobia and propionate-producing bacteria Bacteroides and Akkermansia ( Zhang et al, 2021b ).…”
Section: Hfd-induced Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…bioactive compounds, such as proteins, iodine, vitamins, and polysaccharides, has shown efficacy in the prevention and treatment of lifestyle-related diseases, including hyperlipidemia, [10] obesity, [11] cancer, [12] and others. [13] In the present study protocol, we will systematically review randomized controlled clinical and experimental studies to summarize the current evidence on the efficacy and safety of LJP for the treatment of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“… [7] The brown seaweed Laminaria japonica (LJP), also known as kelp, sea tangle, kombu or kunbu in Japanese and Dashima in Korea, is a traditional medicine and food in Asia because of its pharmacological and biochemical properties. [ 8 , 9 ] LJP containing various bioactive compounds, such as proteins, iodine, vitamins, and polysaccharides, has shown efficacy in the prevention and treatment of lifestyle-related diseases, including hyperlipidemia, [10] obesity, [11] cancer, [12] and others. [13] …”
Section: Introductionmentioning
confidence: 99%